1983
DOI: 10.1038/sc.1983.35
|View full text |Cite
|
Sign up to set email alerts
|

Suprapubic catheterisation after spinal cord injury: a follow-up report

Abstract: The spinal injury patients who were initially treated by suprapubic catheterisation and reported from this unit in 1976 have been reviewed. Fifteen had died by early 1982; only in two cases from renal causes. All but one of the 23 survivors seen has a normal blood urea, and 15 have normal intravenous pyelograms. Eight patients have abnormal IVPs; the abnormalities were insignificant in four, and have been treated in two. Two patients have unilateral nonfunctioning kidneys. These results suggest that no long te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

1991
1991
2008
2008

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 9 publications
0
8
0
2
Order By: Relevance
“…In this study just fewer than 50% of the patients were females with a similar outcome. Suprapubic catheters have been used with success in the early management of traumatic spinal cord lesions 9 and compared by prospective study with CISC for this use 10 with no reported di erence between the two methods of management, although SPC was found to be a cheaper alternative.…”
Section: Discussionmentioning
confidence: 99%
“…In this study just fewer than 50% of the patients were females with a similar outcome. Suprapubic catheters have been used with success in the early management of traumatic spinal cord lesions 9 and compared by prospective study with CISC for this use 10 with no reported di erence between the two methods of management, although SPC was found to be a cheaper alternative.…”
Section: Discussionmentioning
confidence: 99%
“…6 SPC has also been successfully used in the early treatment of spinal cord lesions. 7 Despite purported benefits and convenience of SPC, early studies demonstrating accelerated renal deterioration [8][9][10][11] relegated it to a second-line management option. Long-term complications associated with indwelling urinary catheters are well reported elsewhere, 12 with studies demonstrating proportionately more renal and other urologic complications with long-term (>10 years) than short-term (removed just after injury).…”
Section: Suprapubic Cystostomy For the Neuropathic Bladdermentioning
confidence: 99%
“…On the other hand, continuous suprapubic cystostomy may cause various but not fatal ill effects [2]. We analyzed the long-term outcome of these patients including their backgrounds and complications.…”
Section: Introductionmentioning
confidence: 99%